Synthesis and Immunological Evaluation of Disaccharide Bearing MUC-1 Glycopeptide Conjugates with Virus-like Particles - Wu, Xuanjun (ACS Chem Biol, 2019)
Mucin-1 (MUC1) is a highly attractive antigenic target for anticancer vaccines. Naturally existing MUC1 can contain multiple types of O-linked glycans, including the Thomsen–Friedenreich (Tf) antigen and the Sialyl Thomsen-nouveau (STn) antigen. In order to target these antigens as potential anticancer vaccines, MUC1 glycopeptides SAPDT*RPAP (T* is the glycosylation site) bearing the Tf and the STn antigen, respectively, have been synthesized. The bacteriophage Qβ carrier is a powerful carrier for antigen delivery. The conjugates of MUC1-Tf and -STn glycopeptides with Qβ were utilized to immunize immune-tolerant human MUC1 transgenic (MUC1.Tg) mice, which elicited superior levels of anti-MUC1 IgG antibodies with titers reaching over 2 million units. The IgG antibodies recognized a wide range of MUC1 glycopeptides bearing diverse glycans. Antibodies induced by Qβ-MUC1-Tf showed strongest binding, with MUC1-expressing melanoma B16-MUC1 cells, and effectively killed these cells in vitro. Vaccination with Qβ-MUC1-Tf first followed by tumor challenge in a lung metastasis model showed significant reductions of the number of tumor foci in the lungs of immunized mice as compared to those in control mice. This was the first time that a MUC1-Tf-based vaccine has shown in vivo efficacy in a tumor model. As such, Qβ-MUC1 glycopeptide conjugates have great potential as anticancer vaccines.